The Effectiveness of Land Registration - Riski Amaliyah (Sultan Agung Notary Law Review, 2020)
This research was motivated by the ineffectiveness of land registration that occurred in Tegal City. This is indicated by the fact that there are six thousand land parcels that have not been certified in twenty-seven sub-districts of the four sub-districts in Tegal. Apart from that, the ineffectiveness of the implementation of land registration in Tegal City is caused by various other factors. The problem formulations to elaborate on the above problems are as follows: 1. How is land registration in Tegal City currently implemented? 2. What are the factors that influence the effectiveness of land registration in Tegal City? 3. How is the implementation of land registration in Tegal City effective in the future? The approach method used in this research is normative juridical. The results showed that: 1.the implementation of land registration at the Tegal City Land Office has not been effective. This is evidenced by the large number of uncertified or unregistered lands based on data from the Tegal City Medium Term Development Plan (RPJMD) 2014-2019 and the author's interview with the Head of the Tegal City Land Office. 2. The factors that cause the ineffective implementation of land registration at the Tegal City Land Office are Historical Land Ownership Factors, Community Psychological Factors, Weakness Factors in Land Registration Rules, Implementing and Implementing Factors, and Tax Intervention Factors and others. 3. Efforts that can be made so that the implementation of land registration in the future will run effectively is to make improvements to the components of the legal structure, legal substance and legal culture in accordance with the theory of the legal system of Lawrence M. Friedman.